TINGKAT KETERAMPILAN SERVIS BAWAH BOLA VOLI MINI SISWA KELAS V SEKOLAH DASAR NEGERI 13 BENGKULU TENGAH - Ajis Sumantri (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to determine the skill level of mini volleyball underhand serve skills of fourth grade students of SD Negeri 13 Central Bengkulu for the 2019/2020 academic year. This type of research is descriptive quantitative using survey methods and data collection technique used were tests and measurements. The results of this study were based on the underhand serve skill test of which was categorized very high, namely 2 people (8%), high category namely 3 people (12%), and moderate category namely 13 people (52%), and the low category was 7 people (28%), and the very low category was 0 people (0%). Based on the results above, it can be concluded that the underhand serve skills of fourth grade students of SD Negeri 13 Central Bengkulu in the academic year of 2019/2020, the results of the underhand serve test were obtained with an average of 12.6 and were in the moderate category.